Effect of manganese oxide on the sinterability of 8mol% yttria-stabilized zirconia - Chong F.D.; Tan C.Y.; Singh R.; Muchtar A.; Somalu M.R.; Ng C.K.; Yap B.K.; Teh Y.C.; Tan Y.M. (Elsevier Inc., 2023)
Doping (additives); Fracture toughness; Grain growth; Manganese; Manganese oxide; Mechanical properties; Milling (machining); Particle size; Phase stability; Silicate minerals; Sintering; Vickers hardness; Yttrium alloys; Zirconia; Dopant content; Fracture toughness values; Milling process; Powder particles; Relative density; Sinterability; Sintered samples; Sintering temperatures; Yttria stabilized zirconia